2011
DOI: 10.4236/jcdsa.2011.13016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dental Fluorosis in Mianwali and Mardan Districts

Abstract: This study was conducted to assess the level of dental flourosis and Decaying, Missing, Filled Tooth (DMFT) of selected patients, in district Mardan village Rustam and District Mianwali village Harnoli. Study was conducted among people of age 10 - 60 years. The regions of Rustam and Harnoli are known to have high value of fluoride in drinking water. A cross sectional study was conducted among the subjects and the grade of fluorosis was calculated according to Deans Fluorosis Index. DMFT of each subject was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A study conducted in MianWali and Murdan stated the prevalence of dental fluorosis as 98%, this result is in approximation with our result. 19 On more study with this outcome in children of 12 year of age. 23 As we examined the individuals not only from the Sammo Rind village but also the unexposed group of Gadap town of Karachi, the result showed that in spite of having similarity in eating style and life style of both groups of same ethnicity, the difference in the prevalence of dental fluorosis is due to the level of ground water fluoride ion concentration.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A study conducted in MianWali and Murdan stated the prevalence of dental fluorosis as 98%, this result is in approximation with our result. 19 On more study with this outcome in children of 12 year of age. 23 As we examined the individuals not only from the Sammo Rind village but also the unexposed group of Gadap town of Karachi, the result showed that in spite of having similarity in eating style and life style of both groups of same ethnicity, the difference in the prevalence of dental fluorosis is due to the level of ground water fluoride ion concentration.…”
Section: Discussionmentioning
confidence: 95%
“…Studies from Lahore, MianWali and Murdan and Quetta reported the prevalence of dental fluorosis. [19][20][21][22] Study by Rizwan et al in 2012 in Lahore dental Hospital, patients coming for dental problems were examined and the frequency of dental fluorosis was found to be 12 %. 20 This result is much lower than the result of our study, may be due to level of fluoride ion in drinking water is not as high as in Thar area.…”
Section: Discussionmentioning
confidence: 99%